Population pharmacokinetics study of tacrolimus in liver transplant recipients: a comparison between patients with or without liver cancer before surgery - Bai, Haihong; Yun, Juping; Wang, Zihe; Ma, Yingmin; Liu, Wei (Frontiers in Pharmacology, 2024)
Background and Objective: The main challenge for immunosuppressive therapy of tacrolimus in liver transplantation is the considerable variability in oral bioavailability and the narrow treatment range. Many population pharmacokinetic (PopPK) models have been established to precisely estimate the PK variability of tacrolimus in liver transplant recipients. However, it remains unclear whether there is a significant difference in the PK behavior of tacrolimus between patients with or without liver cancer before surgery. Therefore, we aimed to compare the differences of PK parameters and simulate exposures of tacrolimus between populations of preoperative diagnosed with liver cancer or not by PopPK modeling.Method: In total, 802 blood concentrations of tacrolimus from 196 patients (118 liver cancer and 78 non-liver cancer) were included in this study. Demographic data and clinical parameters were integrated to perform a PopPK analysis using nonlinear mixed-effects modeling approach. Potential covariates were evaluated by using a stepwise method. Goodness-of-fit plot and bootstrap were performed to assess model stability and predictive performance. Simulations were introduced to optimize dosing regimens of both liver cancer or non-liver cancer groups according to the guidance.The PK of tacrolimus was best described by a one compartment model with first order absorption and linear elimination, with weight and direct bilirubin as the significant covariates. In the process of constructing the basic model, we tried to separately estimate the PK parameters of liver cancer and non-liver cancer populations. The results showed that the PK parameters of the two populations were similar, and the individual variation of Ka in non-liver cancer subjects was large.Hence, the final model did not distinguish between the two populations. Moreover, a minor increase but less than 10% was observed in simulated exposure in the patients preoperative diagnosed with liver cancer comparing with non-liver cancer groups.The established PopPK model was capable of optimizing tacrolimus dosing in whole populations who underwent liver transplantation. Although minimal difference was found in tacrolimus exposure between the liver cancer and non-liver cancer groups, more research is warranted to explore the differences between the two populations in the future, given the potential limitations of this study.